MENJAWAB KESENJANGAN TEORI DAN PRAKTIK: PEMBELAJARAN PEDAGOGIK CALON GURU MELALUI LESSON STUDY - Yuswa Istikomayanti; Mashuri Mashuri (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
Pedagogic skills are not obtained instantly by prospective teachers if they only study learning theories. The facts in the microteaching class, although they have understood constructivism theory, they find it difficulty to initiate constructive learning instruction. Through Lesson Study practice, collaboration between teachers and prospective teachers in lesson planning is expected to raise a focus on important points in each stage of learning (pedagogic skills). The comments of prospective teachers are recorded, analysis of field notes, and also see phase with reflection are documented. Student prospective teachers self-assessment data on planning, observation, and reflection skills as supporting as quantitative data. The result is that prospective teachers reach the very good category in compiling a lesson plan, while the aspects of skills to observe and reflect on learning are in the medium and low categories. The implications of pedagogic learning through lesson study are discussed in this article. Kata Kunci :kolegialitas, lesson study, mahasiswa calon guru, rencana pembelajaran.